Integration and Cooperation in Public Hospitals - Eric Rehn (Lund University, School of Economics and Management, Department of Economics, 2010)
Hospital care is a joint production involving a wide range of services; ranging from medical services to support services to hotel services. This paper, focusing on the cooperation between these services, models the internal organization of public hospitals. The analysis is based on the property rights approach to organization (aka the Grossman-Hart-Moore model) and adopts it to the realities of public hospitals. Some institutional features from the Swedish hospital sector are presented to support the analysis, but the results are general. It is found that support services should be integrated into the medical specialities and that hotel services should be outsourced by the hospital. Moreover, it is found that cooperating medical specialities should be integrated, giving support to the use of multi-skilled teams suggested by the advocates of lean health care.
Keywords: D23; I11; I18; 330; Public Hospitals; Property Rights Approach; Joint Production; Integration; Bargaining; Lean Health Care